PENERAPAN MODEL COOPERATIVE LEARNING TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI - Dwi Subekti (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
The purpose of this classroom action research is to know the improvement of learning outcomes in Economics Class XI IPS SMA Negeri N 1 Bantul Lesson Year 2015/2016 through the application of Cooperative Learning Model Course Course Horay Type. Data collection of student learning activities using the instrument of social attitude assessment, instrument of competence assessment of individual behavioral skills in group discussion, group appraisal instrument, reflection sheet, and result of economic learning by test. Activity of teacher by using observation instrument of teaching and learning process. Data analysis method used in this research is quantitative descriptive with percentage. The result of the research shows that there is an increase of learning result in Economics Class XI IPS SMA Negeri N 1 Bantul Lesson Year 2015/2016 has increased 13,88% from pre cycle to cycle 1, and 3,16% from cycle 1 to cycle 2. From pre Cycle to cycle 2 increase of 17.51%. In the pre cycle there are 12 students who have not reached the Minimum Exhaustiveness Criteria (KKM), in cycle 1 there are 2 students who have not achieved the Minimum Exhaustiveness Criteria (KKM) and in cycle 2 all learners have reached the Minimum Exhaustiveness Criteria/ Kriteria Ketuntasan Minimal (KKM) . Based on the observation of the application of Cooperative Learning Model Type Course Horay Course, student learning outcomes are more improved.